(untitled) (diségno, 2025)
This paper examines the communication of cognitive and emotional elements between a drafter and an observer through drawings. Although this topic has been explored from philosophical and psychological perspectives, it still lacks sufficient scientific evidence to determine its biological foundations. Electroencephalography (EEG) is now a recognized instrumental tool that can be used to assess the cognitive and emotional engagement of both the drawing’s creator and its viewer. This study reports the results of experiments in which EEG recordings were made from four subjects who acted as both drafters and observers of drawings with presumed differences in cognitive-emotive content. As drafters, the participants were asked to create both a freehand drawing and a CAD version of an architectural landscape. It was hypothesized that the freehand version would carry a stronger cognitive-emotive charge than the CAD one. Qualitative and quantitative analyses of the EEG data showed that both drafters and observers exhibited parallel responses to the same image. These findings provide experimental support for the theory that specific feelings and perceptions of the drafter are transmitted to the observer, who responds as if him/herself were the author of the drawing.